Perspectives for Space Law in the Twenty-First Century - Hobe, Stephan, (The Pocket Books of The Hague Academy of International Law / Les livres de poche de l'Académie de droit international de La Haye ;, 2025)
The course evaluates the different phases of the development of space law against the background of the development of public international law. An analysis of current international space law investigates whether the body of law is ready for the challenges of outer space commercialisation and the rise of "New Space" in the 21st century. To accomplish this, it peruses through existing space law treaties, in particular the foundational Outer Space Treaty, as well as other sources of space law. Discovering that international space law developed as a permissive law that would enable the further evolution of space technology yet with sufficient foresight to understand that such evolution will require provisions for the preservation of the international common that is outer space, the author examines several avenues for the future evolution of space law. Among these, the author proposes several notions in order to preserve space law's initial character as a law for the protection of the international commons of "outer space" on the one hand, and pay attention to an equitable distribution of the benefits derived from the resources of outer space on the other hand.